Psychophysiological Associations with Gastrointestinal Symptomatology in Autism Spectrum Disorder. Issue 2 (20th June 2016) - Ferguson, Bradley J.; Marler, Sarah; Altstein, Lily L.; Lee, Evon Batey; Akers, Jill; Sohl, Kristin; McLaughlin, Aaron; Hartnett, Kaitlyn; Kille, Briana; Mazurek, Micah; Macklin, Eric A.; McDonnell, Erin; et al.
Abstract : Autism spectrum disorder (ASD) is often accompanied by gastrointestinal disturbances, which also may impact behavior. Alterations in autonomic nervous system functioning are also frequently observed in ASD. The relationship between these findings in ASD is not known. We examined the relationship between gastrointestinal symptomatology, examining upper and lower gastrointestinal tract symptomatology separately, and autonomic nervous system functioning, as assessed by heart rate variability and skin conductance level, in a sample of 120 individuals with ASD. Relationships with co‐occurring medical and psychiatric symptoms were also examined. While the number of participants with significant upper gastrointestinal tract problems was small in this sample, 42.5% of participants met criteria for functional constipation, a disorder of the lower gastrointestinal tract. Heart rate variability, a measure of parasympathetic modulation of cardiac activity, was found to be positively associated with lower gastrointestinal tract symptomatology at baseline. This relationship was particularly strong for participants with co‐occurring diagnoses of anxiety disorder and for those with a history of regressive ASD or loss of previously acquired skills. These findings suggest that autonomic function and gastrointestinal problems are intertwined in children with ASD; although it is not possible to assess causality in this data set. Future work should examine the impact of treatment of gastrointestinal problems on autonomic function and anxiety, as well as the impact of anxiety treatment on gastrointestinal problems. Clinicians should be aware that gastrointestinal problems, anxiety, and autonomic dysfunction may cluster in children with ASD and should be addressed in a multidisciplinary treatment plan. Autism Res 2017, 10: 276–288 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.